2003
DOI: 10.1093/jn/133.8.2565
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Phylloquinone Depletion and Repletion in Older Women

Abstract: Biological markers indicative of poor vitamin K status have been associated with a greater risk for hip fracture in older men and women. However, the dietary phylloquinone intake required to achieve maximal carboxylation of hepatic and extrahepatic vitamin K-dependent proteins is not known. In an 84-d study in a metabolic unit, 21 older (60-80 y) women were fed a phylloquinone-restricted diet (18 micro g/d) for 28 d, followed by stepwise repletion of 86, 200 and 450 micro g/d of phylloquinone. Plasma phylloqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
104
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(109 citation statements)
references
References 20 publications
2
104
1
2
Order By: Relevance
“…According to DRIs for Japanese (2015), the AI of vitamin K for Japanese men and women aged over 18 y was set at 150 mg/d in terms of maintaining blood coagulation (3). However, a previous study suggested that the amount of vitamin K required for maintaining bone health is higher than the amount required for blood coagulation (6). Indeed, in our previous study, the serum concentrations of undercarboxylated OC (ucOC) in healthy postmenopausal Japanese women with around 250 mg/d of vitamin K intake were nearly at fracture-inducing levels of ucOC.…”
Section: S140mentioning
confidence: 73%
“…According to DRIs for Japanese (2015), the AI of vitamin K for Japanese men and women aged over 18 y was set at 150 mg/d in terms of maintaining blood coagulation (3). However, a previous study suggested that the amount of vitamin K required for maintaining bone health is higher than the amount required for blood coagulation (6). Indeed, in our previous study, the serum concentrations of undercarboxylated OC (ucOC) in healthy postmenopausal Japanese women with around 250 mg/d of vitamin K intake were nearly at fracture-inducing levels of ucOC.…”
Section: S140mentioning
confidence: 73%
“…It is therefore possible that current recommended intakes, although adequate to maintain full carboxylation of vitamin K-dependent coagulation proteins (Suttie et al, 1988), are insufficient to maintain other VKD proteins, including osteocalcin, in the fully carboxylated state (Binkley et al, 2000(Binkley et al, , 2002Booth et al, 2003b). Partly in recognition of this, recommended intakes in the United States have recently been increased to 90 and 120 mg/day for women and men, respectively (Institute of Medicine, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…ucOC concentration in serum has been proposed as a sensitive biomarker of vitamin K status, possibly more informative than prothrombin measurement, which assesses hepatic vitamin K status only, and plasma phylloquinone, which is responsive to recent diet [3,7,8] . The responsiveness of the carboxylation status of osteocalcin to vitamin K depletion and repletion has been demonstrated in several trials [9][10][11] . Elevated concentrations of ucOC are associated with increased hip fracture risk [12][13][14] and reduced bone mineral density [15,16] .…”
Section: Introductionmentioning
confidence: 99%